Risk factor analysis of Campylobacter spp., Listeria monocytogenes and Salmonella spp. in the chicken meat value chain - Sneha, Elisetty Naga Pavana; Sanjumon, Ekkoruparambil Sethurajan; Nguyen-Viet, Hung; Dubal, Zunjar Baburao; Bhilegaonkar, Kiran Narayan; Ayoub, Haris; Grace Randolph, Delia; Akash, Bhuva; Gangwar, Amit; Manoj, Sukanna; Premkumar, Dharavath; Dhanze, Himani; et al. (Frontiers in Microbiology, 2026)
IntroductionA cross-sectional study was conducted to evaluate microbiological risk factors associated with Salmonella spp., Campylobacter spp., and Listeria monocytogenes along the chicken meat value chain in Bareilly district, Uttar Pradesh, India.MethodsFollowing multistage cluster sampling design a total of 941 samples from three nodes (retailers, restaurants, consumer households) were collected. The retailers’ samples (n = 519) included raw meat (n = 360), water (n = 83) and swabs (n = 76). The restaurants samples (n = 242) and consumer households (n = 180) were cooked chicken meat samples. Isolation followed ISO-based culture methods with PCR confirmation; presence of any target pathogen was combined into a binary “pathogen indicator.” A structured questionnaire was used to collect information regarding the practices of the retailers (n = 127), restaurant owners (n = 101) and chicken meat consumers (n = 180). Univariate analysis was performed between the factors and presence of pathogen indicator. The factors with p < 0.2 were used in multivariable logistic regression to identify independent predictors of contamination at each node.ResultsAt the retail level, significant risk factors included unclean costumes (OR = 2.130, 95% CI, 1.348–3.367) and selling chicken meat in open space (OR = 1.675, 95% CI, 1.063–2.640). Conversely, trimmed nails (OR = 0.247, 95% CI, 0.154–0.398) and using glass covers (OR = 0.636, 95% CI, 0.404–1.00) for retail outlets were protective factors. At the restaurant level, using raw vegetables as garnish (OR = 4.257, 95% CI, 1.181–15.345) had significantly higher odds of pathogen presence. Protective factors included using separate cutting boards or knives (OR = 0.153, 95% CI, 0.052–0.447) and keeping bulk-cooked products hot (OR = 0.322, 95% CI, 0.113–0.920). At the consumer level, washing hands only before handling (OR = 12.60, 95% CI, 3.124–50.82) was found to be a significant risk factor. Protective factors included using separate cutting boards/knives for raw meat and vegetables (OR = 0.067, 95% CI, 0.017–0.262) and adding raw vegetables during cooking instead of adding after cooking (OR = 0.175, 95% CI, 0.052–0.585).DiscussionFindings indicate that retail-stage infrastructure and hygiene practices are primary drivers of contamination, and that pragmatic interventions are likely to reduce downstream foodborne risk.